2015
DOI: 10.1210/jc.2014-3787
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality Associated With Hypopituitarism in Adults: A Meta-Analysis of Observational Studies

Abstract: Hypopituitarism may increase premature mortality in adults. Mortality benefit from GH replacement in hypopituitarism is less pronounced in women than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 32 publications
3
54
0
4
Order By: Relevance
“…In accordance with previous epidemiological studies on mortality in patients with hypopituitarism (3,6), young patients with NFPAs were shown to be especially exposed with 3 to 6 times increased incidences of type 2 diabetes mellitus, cerebral infarction and sepsis. Even though the number of individual cases with these comorbidities was relatively small, and the 95% CIs were consequently wide, preventive measures for patients diagnosed with NFPAs at young age should not be underestimated.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In accordance with previous epidemiological studies on mortality in patients with hypopituitarism (3,6), young patients with NFPAs were shown to be especially exposed with 3 to 6 times increased incidences of type 2 diabetes mellitus, cerebral infarction and sepsis. Even though the number of individual cases with these comorbidities was relatively small, and the 95% CIs were consequently wide, preventive measures for patients diagnosed with NFPAs at young age should not be underestimated.…”
Section: Discussionsupporting
confidence: 89%
“…Hypopituitary patients have excess vascular mortality and increased occurrence of the metabolic syndrome, diabetes mellitus, cardiac diseases and non-fatal stroke (1,2,3,16,18,19). The reason for this is probably multifactorial, with non-physiologic glucocorticoid replacement, untreated growth hormone deficiency and undertreatment with sex steroids being suggested explanations (2,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term studies on the effect of GH replacement therapy have since shown an improvement in many of these features, such as improved lean body mass, decreased body fat, beneficial effects on plasma lipids, positive effects on intima media thickness, improvement in bone mineral density, and better quality of life [15]. Lately, partly due to a recently published study, a growing body of evidence is showing that GH replacement therapy is associated with reduced excess mortality or normalized mortality compared to the general population [5,16]. We have shown that GH replacement therapy is associated with normalized mortality among over 400 non-functioning pituitary adenoma patients receiving or not receiving GH replacement, who were followed for 10 years [5].…”
mentioning
confidence: 99%